Risperidone Effects on Brain Dynamic Connectivity– a Prospective Resting State fMRI Study in Schizophrenia - Lottman, Kristin K.; Kraguljac, Nina V.; White, David M.; Morgan, Charity J.; Calhoun, Vince D.; Butt, Allison; Lahti, Adrienne C. (Frontiers in Psychiatry, 2017)
Resting-state functional connectivity studies in schizophrenia evaluating average connectivity over the entire experiment have reported aberrant network integration, but findings are variable. Examining time-varying (dynamic) functional connectivity may help explain some inconsistencies. We assessed dynamic network connectivity using resting-state functional MRI in patients with schizophrenia, while unmedicated (n=34), after one (n=29), and six weeks of treatment with risperidone (n=24), as well as matched controls at baseline (n=35) and after six weeks (n=19). After identifying 41 independent components (ICs) comprising resting-state networks, sliding window analysis was performed on IC timecourses using an optimal window size validated with linear support vector machines. Windowed correlation matrices were then clustered into 3 discrete connectivity states (a relatively sparsely connected state, a relatively abundantly connected state, and an intermediately connected state). In unmedicated patients, static connectivity was increased between five pairs of ICs and decreased between two pairs of ICs when compared to controls, dynamic connectivity showed increased connectivity between the thalamus and somatomotor network in one of the three states. State statistics indicated that, in comparison to controls, unmedicated patients had shorter mean dwell times and fraction of time spent in the sparsely connected state, and longer dwell times and fraction of time spent in the intermediately connected state. Risperidone appeared to normalize mean dwell times after six weeks, but not fraction of time. Results suggest that static connectivity abnormalities in schizophrenia may partly be related to altered brain network temporal dynamics rather than consistent dysconnectivity within and between functional networks and demonstrate the importance of implementing complementary data analysis techniques. Clinical trials registration: Registry Name: Treatment Response in Schizophrenia: Bridging Imaging and Postmortem Studies URL: https://clinicaltrials.gov/ct2/show/NCT00937716?term=NCT00937716&rank=1 Registration Number: NCT00937716